Researching AIDS, sexuality and gender : case studies of women in Kenyan universities - Kamau, Nyokabi (UPCC book collections on Project MUSE. Global Cultural Studies., 2013)
The HIV and AIDS regime of the early twenty-first century has opened up unknown vistas in intellectual pursuits and knowledge creation. One such newly opened area of research is studying HIV and AIDS in relation to gender issues. However, owing to the devastating nature of the epidemic, most studies tend to focus on women merely as an "at-risk" population - leaving aside the wider sociological dimensions that pertain to women's sexuality in general, issues of AIDS related stigma, and discrimination and how it impacts on women's careers as economic contributors to society. The uniqueness of the present study lies in the fact that it embodies the author's triangulated research into the tripartite dimensions of HIV and AIDS, women's sexuality, and gender-sociology, all against the backdrop of analysing actual experiences of career women in Kenyan universities.